2023
DOI: 10.1111/ctr.15077
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of low attenuation area on computed tomography detects chronic lung allograft dysfunction, especially bronchiolitis obliterans syndrome, after bilateral lung transplantation

Abstract: IntroductionThe percentage of low attenuation area (%LAA) on computed tomography (CT) is useful for evaluating lung emphysema, and higher %LAA was observed in patients with chronic lung allograft dysfunction (CLAD). This study investigated the relationship between the %LAA and the development of CLAD after bilateral lung transplantation (LT).MethodsWe conducted a single‐center retrospective study of 75 recipients who underwent bilateral LT; the recipients were divided into a CLAD group (n = 30) and a non‐CLAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The consolidations and pleural effusions were risk factors for death on follow-up CT scan [8]. Kubo et al [9] found that the percentage of low attenuation areas on expiratory CT scan can detect CLAD and especially BOS early. CT screening of the donor organ and identifying pulmonary abnormalities in the graft even before the lung transplant was performed, resulted in identifying patterns via machine learning that were indicative of a 19 times increased risk of CLAD development [10].…”
Section: Diagnosis Of Chronic Lung Allograft Dysfunctionmentioning
confidence: 99%
“…The consolidations and pleural effusions were risk factors for death on follow-up CT scan [8]. Kubo et al [9] found that the percentage of low attenuation areas on expiratory CT scan can detect CLAD and especially BOS early. CT screening of the donor organ and identifying pulmonary abnormalities in the graft even before the lung transplant was performed, resulted in identifying patterns via machine learning that were indicative of a 19 times increased risk of CLAD development [10].…”
Section: Diagnosis Of Chronic Lung Allograft Dysfunctionmentioning
confidence: 99%